Asymmetric Total Synthesis of Ventilanones A and B, Two Naturally Occurring Pyranonaphthoquinones from Ventilago harmandiana - Deelertpaiboon, Pramchai; Kongsriprapan, Sopanat; Krajangsri, Suppachai; Betterley, Nolan M.; Kuhakarn, Chutima; Reutrakul, Vichai (Synthesis, 2022)
The asymmetric synthesis of the novel pyranonaphthoquinones ventilanone A and ventilanone B, isolated from the Thai endemic plant Ventilago harmandiana, is accomplished by employing l-rhamnose and gallic acid as the starting materials. The key reactions are the utilization of a newly introduced reagent, PhSCF2H/SnCl4, for the formylation of sterically hindered aromatics containing an electron-withdrawing methyl ester, and the efficient Hauser annulation of phenylthiophthalides with optically active C-1 glycals derived from l-rhamnose. The developed synthetic methodologies solve the long-standing problem of the formylation of sterically hindered aromatics containing electron-withdrawing groups, and are applicable for the synthesis of other analogues with substituents on the aromatic and pyran rings.
Keywords: total synthesis; Hauser annulation; pyranonaphthoquinones; natural products; Ventilago harmandiana Pierre; ventilanones